Ureltu's Ewenki narratives and the crisis of minority cultures in China. (January 2020) - Xiaofeng, Li; Yanjun, Liang
The author Ureltu has undergone a transformation from novelist to producer and disseminator of Ewenki historical culture, moving from fictional Ewenki stories of forty years ago to recent non-fictional Ewenki historical narratives. In the course of this transformation, he has provided a sample of Ewenki culture that, on the one hand, can break down misunderstandings of the culture and, on the other, can revitalise a recognition of Ewenki cultural values. He has used those examples to include reflection on knowledge and power as it plays out in the current cultural crisis of other ethnic minorities in China. He speaks of the identity consciousness of a 'cultural chain' that extends beyond Ewenki culture to the inheritance of Chinese culture as a whole.